Keefektifan Injeksi Toksin Botulinum Tipe A (BTX-A) untuk Terapi Neuralgia Pasca Herpes: Sebuah Tinjauan Pustaka - Wijaya, Edward; Winaya, Ketut Kwartantaya; Utami, Desak Nyoman Trisepti (Fakultas Kedokteran Universitas Trisakti, 2025)
Postherpetic neuralgia (PHN) is a common and debilitating complication of shingles, characterized by persistent pain that lasts for months to years after the resolution of the herpes zoster rash. While various treatments, such as anticonvulsants and opioids, are commonly used, they often fail to provide adequate pain relief and are associated with significant side effects. Botulinum toxin type A (BTX-A), traditionally used for muscle spasticity, has emerged as a promising treatment for PHN due to its ability to reduce pain through its neurotoxic effects. This literature review evaluates the safety and efficacy of BTX-A in treating PHN by reviewing 30 studies sourced from databases such as PubMed, Medline, and PubMed Central. The results indicate that BTX-A injections significantly alleviate PHN-associated pain, with many patients experiencing a reduction of up to 70% in pain severity. Additionally, BTX-A has been shown to improve patients' quality of life by enhancing sleep quality and reducing the need for oral medications. Although the results are promising, the review calls for further research to determine optimal dosing protocols and the long-term effects of BTX-A. Despite its limitations, BTX-A presents a potential therapeutic option for managing PHN, particularly for patients who do not respond well to traditional treatments.